PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS IV SD NEGERI 009 BINIO JAYA KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Sohorma Sohorma; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve student learning outcomes IPS Class IV Elementary School 009 Binio Jaya with the application model Think Pair Share (TPS) in the academic year 2014/2015. The subjects were fourth grade students of SD Negeri 009 Binio Jaya totaling 30 people. The students consisted of 12 male students and 18 female students. This study is a Class Action Research (Classroom Actions Research) which comprises two cycles. Based on the results of research and data analysis known that the activity of teachers increased in the first cycle to the meeting-1 activity teachers acquire 68,89% success with sufficient criteria. In the first cycle of the 2nd meeting of the success of the activity of teachers is 80% with good criteria. In the second cycle to-one meetings to acquire 87.78% success criteria very well. In the second cycle of the 2nd meeting increased to 88.89% with excellent qualifications. Meanwhile, the activities of students in the first cycle-1 meetings to obtain a 67.78% success. In the first cycle of the 2nd meeting of success increased to 71.11%. Implementation of the second cycle-1 meetings to be 77.78% with good qualifications. In the second cycle of the 2nd meeting increased 91.11% with excellent qualifications. In addition, student learning outcomes before implementation of cooperative learning model TPS is 61.67 with sufficient number of qualified students who complete 13 people (43.33%). At UH 1 first cycle increased to 66.67 (8.11%) the number of students who completed 17 people (56.67%). At UH 2 second cycle increased as much as the average value to 83.5 (25.24%) who completed the number of 30 people (100%). It can be concluded that cooperative learning model TPS can improve student learning outcomes IPS fourth grade N 009 Binio Jaya.Keywords : Cooperative Learning Model TPS, IPS Learning Outcomes